A graph based architectural (Re)configuration language. - Wermelinger, Michel (Software engineering notes.)
For several different reasons, such as changes in the business or technological environment, the configuration of a system may need to evolve during execution. Support for such evolution can be conceived in terms of a language for specifying the dynamic reconfiguration of systems. In this paper, continuing our work on the development of a formal platform for architectural design, we present a high-level language to describe architectures and for operating changes over a configuration (i.e., an architecture instance), such as adding, removing or substituting components or interconnectons. The language follows an imperative style and builds on a semantic domain established in previous work. Therein, we model architectures through categorical diagrams and dynamic reconfiguration through algebraic graph rewriting.